Emerging risk of Dirofilaria spp. infection in shelter dogs in southern Italy - Ciuca, Lavinia; Caruso, Valeria; Illiano, Sergio; Bosco, Antonio; Maurelli, Maria Paola; Rinaldi, Laura (Frontiers in Veterinary Science, 2023)
The aim of the present study was to better investigate the occurrence of Dirofilaria spp. in southern Italy. For this purpose, a local dog shelter in Castel Volturno (Campania region, southern Italy) was selected and screened for the presence of Dirofilaria spp. A total of 260 blood samples were analysed for identification of microfilariae (mff) and detection of Dirofilaria immitis antigen. Dogs were classified according to their age (1-3 years; 4-6 years; 7-11 years; > 11 years) and length of stay in the shelter at the time of sampling (dogs that entered in the shelter in the last four months; dogs housed in the shelter for more than four months up to 2 years; dogs housed for more than 2 years). The modified Knott’s test revealed that 195 dogs (75.0%) were positive for circulating mff of Dirofilaria spp. Specifically, 104/260 (40.0%) dogs were positive for D. immitis and 91/260 (35.0%) were positive for D. repens. In addition, 72/260 (27.7%) dogs had both D. immitis and D. repens mff. Antigen testing revealed that 78/260 (30.0%) dogs were positive for D. immitis. However, 26/104 (25.0%) of the dogs with D. immitis mff were antigen-negative. The overall k concordance between the modified Knott's test and the antigenic test was ≤0.2 (poor) (P = 0.000). The results of the logistic regression model showed a significant association between Dirofilaria exposure and the period of time the dogs had spent in the shelter at the time of sampling. Dogs housed in the shelter for four months (group 1) and between four months and two years (group 2) had higher Dirofilaria positivity than dogs in group 3 (housed for more than 2 years) (80.4% vs 79.6% vs 62.4%, respectively). Moreover, male dogs and older dogs (between 7 and 11 years of age) were more likely to be infected with Dirofilaria spp.